Key players of singlet oxygen-induced cell death in plants - Laloi, Christophe; Havaux, Michel (Frontiers in Plant Science, 2015)
The production of reactive oxygen species (ROS) is an unavoidable consequence of oxygenic photosynthesis. Singlet oxygen (1O2) is a highly reactive species to which has been attributed a major destructive role during the execution of ROS-induced cell death in photosynthetic tissues exposed to excess light. The study of the specific biological activity of 1O2 in plants has been hindered by its high reactivity and short lifetime, the concurrent production of other ROS under photooxidative stress, and limited in vivo detection methods. However, during the last 15 years, the isolation and characterization of two 1O2-overproducing mutants in Arabidopsis thaliana, flu and ch1, has allowed the identification of genetically controlled 1O2 cell death pathways and a 1O2 acclimation pathway that are triggered at sub-cytotoxic concentrations of 1O2. The study of flu has revealed the control of cell death by the plastid proteins EXECUTER (EX)1 and EX2. In ch1, oxidized derivatives of β-carotene, such as β-cyclocitral and dihydroactinidiolide, have been identified as important upstream messengers in the 1O2 signaling pathway that leads to stress acclimation. In both the flu and ch1 mutants, phytohormones act as important promoters or inhibitors of cell death. In particular, jasmonate has emerged as a key player in the decision between acclimation and cell death in response to 1O2. Although the flu and ch1 mutants show many similarities, especially regarding their gene expression profiles, key differences, such as EXECUTER-independent cell death in ch1, have also been observed and will need further investigation to be fully understood.